Students' study interests and satisfaction with study - Palekčić, Marko (Array, 2005)
This study shows the results of an empirical research of the students’ (dis)satisfaction with the organization and contents of their studies, and their study interests. The 411 research subject have been chosen among students from different study groups of the Faculty of Philosophy in Zadar. Most students express a great interest in their studies and a satisfaction with the study contents, but also a dissatisfaction with the organization of their studies. Their study interest positively relates to their satisfaction with the contents, and negatively to their dissatisfaction with the organization of their studies. The students who have enrolled in the desired studies show a greater interest in them. They are also more satisfied with the contents of study and more critical of the organization of their studies, in other words, they are more dissatisfied with the organization of their studies than the students who were forced to enroll in substitute studies, having failed to enroll in the desired studies. The students who would re-enroll in the current studies if given a chance also show a greater interest in and satisfaction with the study contents than the students who would change their current studies if given a chance (i.e. they would not enroll in the same studies again). Male and female students manifest the same interest in their studies and satisfaction with the contents. However, female students are more dissatisfied with the organization of their studies than the male students. The results obtained by this research are comparable to the results of the research conducted by other researchers who start from the same theoretic position (the so-called "The Munich theory of interests") and apply the same or similar instruments for research. These research results are to be studied in the context of the pedagogical and psychological theory of interests and intrinsic motivation, but with the aim of improving the quality of university teaching.